6개월간의 치료적 마사지와 도수신장 치료에 대한 선천성 근성 사경 환아의 유형별 특성 - 김용욱(Yong-Wook Kim); 김민희(Min-Hee Kim) (한국콘텐츠학회 논문지, 10(4), 2010)
The main purpose of this prospective longitudinal study was to evaluate, according to a standard clinical classification and assessment method, the effect of a standardized manual stretching and therapeutic massage program on patients with clearly defined congenital muscular torticollis. A total of 52 cases of congenital muscular torticollis who were first seen when they were less than one year old and were treated with conservative physical therapy. Before treatment, the patients were divided into one of three clinical groups: (1) sternomastoid tumor group, (2) muscular torticollis group, and (3) postural torticollis group. Of the 52 patients, 32 (61.5%) made up the sternomastoid tumor group; 15 (28.9%) the muscular torticollis group; and 5 (9.6%) the postural torticollis group. Multivariate analysis of the outcomes showed that the duration of treatment was significantly differentiated according to the clinical group (p<0.01), age at presentation (p<0.01), and a passive rotation deficit of the neck (p<0.01). The current study showed that well controlled conservative physical therapy is safe and effective in the treatment of congenital torticollis in about 84.6% of patients who are first seen before the age of one year. 본 전향적 종적 연구의 목적은 임상적으로 명확히 구분되어 정의된 각각의 선천성 근성 사경군을 대상으로 표준화된 도수 신장치료와 치료적 마사지를 적용하였을 때 경부에서 나타나는 특성과 회복율을 알아보는 것이다. 생후 1년 미만에 발현하여 보존적 물리치료를 시작한 총 52명의 선천성 근성 사경 환아를 연구 대상으로 하였다. 치료 전, 모든 환아는 다음 세 가지 군으로 분류하였다: (1)종괴군, (2)근성 사경군, (3)체위성 사경군. 총 52명의 환아 중 종괴군이 32명(61.5%); 근성 사경군이 15명(28.9%); 그 외 체위성 사경군이 5명(9.6%)이었다. 다변량 분석 결과를 통해 치료 기간은 종괴성 사경군이 유의하게 길었고(p<0.01), 발현 연령은 종괴성 사경군 $1.65{±}1.31$ 개월로 다른 군에 비해 유의하게 빨랐다(p<0.01), 경부회전 제한에 따라 제한이 클수록 유의하게 회복율의 저하를 보였다(p<0.01). 본 연구의 결과 잘 숙련된 치료사에 의해 시행된 보존적 물리치료는 사경의 치료에 안전하며, 특히 생후 1년 미만에 발현된 선천성 근성 사경 환아의 84.6%에서 좋은 회복율을 보였다.